Training and Development for Barangay Tanod in Response to Inter-Agency Task Force Health Protocol: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The researchers aim to determine Training and development for barangay tanod in response to the Inter-Agency Task Force health protocol during the covid 19 outbreak. Every residence has suffered from the virus since the COVID-19 pandemic at Barangay 178 Camarin Caloocan City. Some of them did not report to work because of the lockdown that the government implemented. The barangay tanod is in charge of implementing the barangay's health protocol because their job includes earning a living, assisting and guiding people, and providing important information about the value of health protocols. This study must determine the importance of training and development for barangay tanod during the covid 19 pandemic. the respondents of this research are the barangay tanod, barangay official and purok leader of Barangay 178 Camarin Caloocan City. The researchers use the descriptive method, which is a type of research used to describe the characteristics of the population. It collects data to answer the question of what, when and how the question pertains to a particular population or group. The researcher interviews the barangay official, tanod, and purok leader. The main instrument in this study is the researcher since the information is primarily gathered through interviews. The researcher also tests paper-like questionnaires to collect the data through answer sheets. Questions were in English, but the researchers were there to guide or explain to ensure that the respondents understood the questions and answered the specific item with the purpose of this study. This study indicated that based on the demographic profile of three respondents,” barangay tanod, barangay officials and purok leaders at Barangay 178 Camarin Caloocan, The majority of the respondents came from the age bracket of 40 and above, male, married and college graduate.in the trainer and lecturer, The purok leader has the highest weighted mean of 4.24, which is very effective. Regarding budget, the highest percentage is barangay with a weighted mean of 4.6, which is very effective. While in the program, the highest percent is barangay tanod weighted mean of 4.63 very effective. The study's finding revealed that barangay officials conducted training and development for barangay tanod in barangay 178 Camarin Caloocan City. Some barangay tanod attend the seminar about properly implementing health protocol and how the barangay tanod executes the safety protocol properly to avoid misunderstanding. The barangay officials must provide seminars for barangay tanod to implement safety health protocol and provide facilities to conduct seminars.